Dramaturgy as “аrt of passions” in poetically represented action. On the theory of drama - Shumakova, Svitlana (ХДАК, 2023)
The current methods of presenting information to society, which are categorically irrevocably rooted in our lives, are characterized by the desire to convey the most extensive amount of data in a super-compressed information framework. Society is confidently and, presumably, purposefully moving towards the world once predicted by Ray Bradbury, in which masterpieces of world classics turn into meaningless five-minute videos, where only names of brilliant works remain.
Keywords: теорія драми; drama theory; dramatic theater